The transdisciplinary health research apparatus: A Baradian account of knowledge boundaries and beyond. (May 2022) - Thorpe, Holly; Clark, Marianne; Brice, Julie; Sims, Stacy
This paper engages with new materialist theory to reimagine transdisciplinary health research. In particular, we draw upon Karen Barad's theory of agential realism and concept of apparatus to rethink the processes of doing transdisciplinary research. A Baradian inspired approach to transdisciplinarity encourages us to not only explore ways of knowing health phenomena differently by working across disciplines, but also to pay close attention to the politics and practices in such research. We offer a case study based on a two-year transdisciplinary research project focused on the health condition known as Low Energy Availability (LEA) in sportswomen. Through this case we highlight three key ways that Barad's concept of apparatus helped us know transdisciplinarity differently: (1) Reading disciplines through each other, (2) Intra-actions and the everyday performativity of disciplinary boundaries, and (3) Troubling the boundaries of the apparatus. Ultimately this paper illustrates the value in feminist new materialist conceptual tools for encouraging different questions of transdisciplinary research as ethico-onto-epistemological practices, processes, and politics of knowledge production.